Market-phase performance of LIC MF Large & Midcap Fund - Sahoo, Saumya Ranjan (Journal of Advanced Research in Accounting and Finance Management, 2020)
MF is set up in the form of a trust. The trust has sponsor, trustee, Asset Management Company (AMC) and custodian. It has to be registered with Securities exchange board of India (SEBI). MF is regulated under the SEBI (MF) Regulation, 1996.Mutual Fund is a tool for small investors and for people who cannot invest directly in equity shares and debt instruments. Small investors can take benefits of stock market growth by investing in equity and debt instruments through MF. Though it is a convenient way of investment for the people who do not have knowledge, time or inclination to invest directly in stocks, it does not guarantee return or value of the original investment. The appreciation of investment depends on the performance of fund and stock market. MFs are Financial Intermediaries that pool the financial resources of investors and invest in diversified portfolio of assets. It is a mechanism for pooling resources by issuing units to the investors and investing funds in securities. It is a vehicle for collective investment, where the unit holders become part owners of the investment done under a scheme. The profit or losses are shared by the investors in proportion to their investments.